Determination of Hydraulic Properties of a Large Self-Propped Hydraulic Fracture in the Geothermal Research Borehole Horstberg Z1 in the Northwest German Basin. (6th November 2019) - Jung, Reinhard; Hassanzadegan, Alireza; Tischner, Torsten
Abstract : The pressure records of an interference test on a huge hydraulic fracture in a layered sedimentary rock formation of the Northwest German Basin were analysed in order to determine fracture transmissivity and fracture storage coefficient. The fracture had been created by injecting some 20, 000 m 3 of freshwater at 3800 m depth in borehole Horstberg Z1 of the geothermal research project GeneSys. Its main purpose is to study the hydraulic properties and mechanical behaviour of artificial fractures kept open by the so called self-propping effect which results from the misfit of the opposite fracture surfaces being sheared during fracture propagation. A diagnosis of the pressure records of the interference test showed that the flow geometry is parallel (vertical linear fracture flow) rather than radial or bilinear. This is explained by assuming a highly conductive flow channel within the fracture resulting from a turn of tensile to mixed-mode fracture propagation. Based on this observation an analytical 1D-model was developed that describes transient fluid-flow in a vertical fracture that is imbedded in impermeable rock and is vertically confined by permeable rock layers. This model was verified by a corresponding 1D-numerical model and was then used to fit the observed pressure records of the constant rate interference test. The fitting procedure yielded a transmissivity of the self-propped fracture in claystone that is more than ten times lower than the transmissivity of self-propped fractures in granite as observed in HDR/EGS systems (Hot-Dry-Rock/Enhanced Geothermal Systems). At the same time it is more than ten times higher than the transmissivity of propped fractures in shale gas reservoirs. The injectivity index of the studied fracture resulting from transmissivity and the high length to height ratio of the fracture enables to circulate water or brine through the fracture at flow rates up to about 0.005 m 3 /s. For the given temperature of about 150°C this would satisfy the heat demand of small to medium size building complexes. Higher flow rates and heat production could be achieved with multiple fractures of this kind. The results obtained in borehole Horstberg Z1 are promising but more in-situ experiments in various rock formations and different stress regimes are necessary to generalize the results.